ANALISIS PENGARUH KUALITAS KINERJA BERKELANJUTAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN KEBERLANJUTAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BERSA EFEK INDONESIA TAHUN 2015 – 2017) - Rr. Adita Khasanah Ghozali; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to help companies demonstrate their responsibilities in the Sustainability Report on the Economy, Social and environmental aspects. Disclosure of Sustainability Reports follows the guidelines of the Global Reporting Initiative (GRI), G4 and G4.1, both of which consist of three main aspects namely Economic performance, Environmental performance and Social performance.  The population in this study consisted of all manufacturing companies in the Indonesia Stock Exchange in the period 2015 - 2017. Sampling was carried out using the purposive sampling method. The total sample of this study was 54 companies. This study uses multiple regression analysis to test hypotheses. The results of this study indicate that disclosure sustainability performance and company size has a positive effect on sustainability disclosures